(untitled) (Revista revoluciones, 2023)
The objective of this work was to characterize the socio-economics of agricultural producers of the Cordillera Chongón Colonche Association after the implementation of the PIDAASSE project. The investigation was based on a mixed approach whose primary source of information was made up of the 28 producers of the Association. To collect the information, the survey was used whose components were: social, economic, agricultural and environmental. In the social aspect, they only have electricity and potable water, most have only basic education, they do not have public transportation or health services; In agricultural aspects, of the 120 hain production, only 34 hectares have irrigation, of which PIDAASSE only supported them with drip irrigation systems for 12 hectares, so the low technological development within the productive units is evident. and poor use of water. In economic aspects, income in rural areas is limited to agricultural production, where 14% of producers choose to rent the land for minimal values; in the environmental aspect, after the implementation of the PIDASSE, they indicate that at present the native species that inhabited the area are no longer frequently observed. The current situation of the productive units, regarding the use of their potentialities visualized in the characterization, raises the importance of promoting sustainability approaches, based on an adequatearticulation of economic, social, environmental and cultural aspects, this perspective must be translated into the definition of criteria for participatory planning in the medium term, with direct actions aimed at the consolidation of sustainable rural development, the use of resources, and the active participation of social actors in determining their future.